2016
DOI: 10.1002/ps.4451
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic neonicotinoid insecticides for the management of the Asian citrus psyllid Diaphorina citri on containerized citrus

Abstract: If the time needed to achieve effective thresholds of a systemic neonicotinoid is known, treatments at production facilities could be scheduled that would minimize unnecessary post-treatment holding periods and ensure maximum retention of effective concentrations after the plants have shipped to retail outlets. The rapid uptake of the insecticides and retention at effective concentrations in containerized citrus suggest that the current 30 day post-treatment shipping restriction from production facilities to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
1
23
0
4
Order By: Relevance
“…Thiamethoxam is a neonicotinoid precursor to clothianidin ( Nauen et al 2003 ) and clothianidin is known to metabolize into TZNG and TZMU ( Kim et al 2012 ). While clothianidin is effective against D. citri , little is known about the influence of specific dosage on D. citri feeding behavior or mortality ( Byrne et al 2017 ). Langdon and Rogers (2017) found that the LC 50 of thiamethoxam and clothianidin to the LS population by ingestion was 0.11 and 0.09 ppm, respectively, while the LC 90 was 4.94 and 9.35 ppm, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thiamethoxam is a neonicotinoid precursor to clothianidin ( Nauen et al 2003 ) and clothianidin is known to metabolize into TZNG and TZMU ( Kim et al 2012 ). While clothianidin is effective against D. citri , little is known about the influence of specific dosage on D. citri feeding behavior or mortality ( Byrne et al 2017 ). Langdon and Rogers (2017) found that the LC 50 of thiamethoxam and clothianidin to the LS population by ingestion was 0.11 and 0.09 ppm, respectively, while the LC 90 was 4.94 and 9.35 ppm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we cannot determine how any one metabolite, including clothianidin, affects D. citri mortality in this study. While understanding the role of each metabolite is beyond the scope of this investigation, it is possible that the combination of multiple metabolites has an additive effect on D. citri mortality as suggested by Byrne et al (2017) . Byrne et al (2017) demonstrated a strong correlation between thiamethoxam and the metabolite, clothianidin, but were unable to determine whether mortality was the result of either thiamethoxam or clothianidin, or a combination of the two.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations